Cross-cultural innovation: enhancing the Japanese Moku-zogan technique - Wan Omar, Wan Noor Faaizah; Subri, Shafilla; Ab Hamid, Abu Hanifa (Universiti Teknologi MARA, Kedah, 2025)
Moku-zogan, a traditional Japanese wood inlay technique, exemplifies meticulous craftsmanship through the inlaying of various woods into surfaces to create intricate designs. Originating from a deep-rooted heritage of Japanese artisanship, this technique not only showcases the precision in woodworking but also embodies significant cultural values, particularly in regions renowned for their skilled artisans like Hakone and Kyoto (Tanaka, 2015). In the modern era, Mokuzogan has embraced significant technological transformations, particularly through the integration of sophisticated algorithms in computer-aided design (CAD) and computeraided manufacturing (CAM). These advancements facilitate the creation of more complex and precise designs, employing algorithms to optimize the fit and arrangement of inlays, thus bridging traditional skills with hightech methods (Sato & Thompson, 2018). In a groundbreaking fusion of cultural identities and craftsmanship, we developed a series of ten console tables utilizing the traditional Japanese Moku-zogan technique, tailored to embody a harmonious blend of Malaysian and Japanese aesthetics. The design process was meticulously structured into several phases, beginning with ideation, where initial concepts were inspired by the unique cultural symbols of both nations.